Adhesion–deformation and dynamic processes in boundary layers - Стельмах, А.У. (Problems of Tribology, 2014)
The test and measuring complex for studying of dynamic processes in boundary layers of lubricant is developed and created. The specialized software is developed and approved. It in aggregate with program modules of mathematical processing of experimental data and graphic interfaces allows to create evident and rather simple automated system of registration of parameters and steering of friction modes.